Penerapan Metode Logika Fuzzy Untuk Alat Kontrol Kelembapan Tanah Pada Greenhouse Laboratorium Tanah BPTP Jawa Timur - Muhammad Rifqi Maulana; Mochammad Hannats Hanafi Ichsan; Sudarmadi Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Plant maintenance has many functions. One of its functions is to help a plant growth analysis. Soil moisture is also an important factor in plant growth. At the time of soil moisture has a dry condition, then the growth of plants will experience a constraint. Conversely, if the soil moisture is good, the plant will grow well. To overcome this required a tool for watering automatically and kontrol based on soil moisture. In this case researchers used the fuzzy method to enable the automatic valve on the ground humidity kontrol tool. As a programming application using NI LabVIEW based on graphical programming with display to monitor soil moisture data. From the test results using fuzzy method with five membership function to provide output in the form of automatic watering to automatic valve using simulation mode on fuzzy Designer calculate soil moisture of 4.8453 and water pressure of 0.776367 produce fuzzy output of 4524.42. So as to produce water watering automatically for 4.5 seconds. These results have been successful in controlling soil moisture.